Determining Factors Influencing Filipinos’ Behavioral Protection against COVID: Integrating Extended Protection Motivation Theory, Theory of Planned Behavior, and Ergonomic Appraisal - Ma. Janice J. Gumasing; Frankern Luis S. Malabuyoc; Ardvin Kester S. Ong; Charmine Sheena Saflor (COVID, 2024)
This study examined the perceived protective behavior of Filipinos towards COVID-19. It utilized the extended protection motivation theory (PMT) and theory of planned behavior (TPB) models with the integration of ergonomic appraisal, applying partial least square structural equation modeling (PLS-SEM) to determine the factors affecting the protective behavior of Filipinos against COVID-19. A questionnaire was developed and distributed to 3000 Filipino citizens to measure the factors and their relationships. Results showed that understanding COVID-19 significantly influences the Filipinos’ perceived virus severity and vulnerability. In turn, perceived severity, self-efficacy, attitude, and subjective norms were the significant factors that affected the behavioral intention, impacting protective behavior. In addition, cognitive and macro ergonomics have been found to be the factors that influence the protective behavior of Filipinos against COVID-19. Thus, the study’s findings can be used as a framework for developing pandemic response initiatives that aim to inform and educate Filipinos, especially those who do not have the privilege of accessing information. Lastly, the outcome of this study can be used as a theoretical framework for future researchers who aim to conduct a study in a similar discipline.